2014
DOI: 10.1590/0100-69912014006007
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-gonadal function in men with liver cirrhosis before and after liver transplantation

Abstract: In a prospective study, serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2) and prolactin (PRL) of 30 male patients with cirrhosis were determined two to four hours before and six months after liver transplantation. The results were compared according to the Model for End-stage Liver Disease (MELD). Results Results ResultsResults Results: male patients with liver cirrhosis have hypogonadism. FSH was normal, but inappropriately low due to androgen failure; E2 and PRL, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
(37 reference statements)
2
15
0
1
Order By: Relevance
“…Estradiol values were decreased after LT in all of the six studies that reported these values . The estradiol reduction ranged from 25.0 to 57.6% .…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Estradiol values were decreased after LT in all of the six studies that reported these values . The estradiol reduction ranged from 25.0 to 57.6% .…”
Section: Resultsmentioning
confidence: 86%
“…. The analysis included ten prospective studies , five retrospective studies and six cross‐sectional studies . Healthy controls were used for comparison in five studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A doença hepática terminal afeta a homeostase no eixo hipotalâmico-hipofisáriogonadal, desencadeando o hipogonodismo, determinado pelo nível baixo de testosterona e nível alto de estrogênio (ZACHARIAS et al, 2014). A fisiopatologia do hipogonodismo em pacientes com doença hepática terminal é complexa, podendo ocorrer por dano no metabolismo, principalmente em pessoas com cirrose por etiologia alcoólica, uma vez que o álcool é responsável por causar insuficiência gonodal primária (BANNISTER et al, 1987).…”
Section: Discussionunclassified